Grazing by the Copepod Parvocalanus crassirostris on Picochlorum sp. at Harmful Bloom Densities and the Role of Particle Size - Ma, Xiao; Jacoby, Charles A.; Johnson, Kevin B. (Frontiers in Marine Science, 2021)
Harmful blooms of nanophytoplankton (2–20 µm) are increasingly common and sometimes severe, but requirements and controls of such blooms (e.g., water quality constraints, requirements for nutrients, and the presence of different guilds of grazers) are poorly understood. Laboratory grazing experiments were conducted to evaluate the potential for top-down control by the copepod Parvocalanus crassirostris on a small HAB species (an unidentified chlorophyte Picochlorum, 1–4 µm) and to test the effects of cell sizes on grazing rates. The Picochlorum sp. is a strain isolated from a long-lasting harmful algal bloom (HAB) in the Indian River Lagoon (IRL) that reached high densities (> 1 × 106 cells ml-1). Experiments contrasted grazing on Picochlorum sp. with grazing on the palatable prymnesiophyte Isochrysis galbana (4–6 µm) in monocultures and mixed cultures. When presented in monocultures, grazing rates on Picochlorum sp. were lower than grazing rates on the palatable alternative. When Picochlorum sp. were presented alongside I. galbana, copepods essentially ceased feeding on the former. In additional experiments, P. crassirostris were fed plastic beads with diameters of 2.0–17.9 µm to control for differences in taste, toxicity, production of mucilage and shape of potential food. Paracalanus crassirostris fed most efficiently on beads with diameters of 7.0–7.9 µm. Results revealed that P. crassirostris can consume Picochlorum sp., but small size and the presence of palatable cells reduces the likelihood of top-down control of blooms of Picochlorum sp.